Comparative Study of Different Packing Designs in Counterflow Wet Cooling Towers - Lee, onn; Ir. Ts. Dr. MOHAMAD FARID BIN SIES (Research Progress in Mechanical and Manufacturing Engineering, 2026)
This study presents a comprehensive comparative analysis of three polyvinyl chloride (PVC)-based packing designs non-uniform film fill (NNU), double S-wave fill (DSW), and expanded wire mesh (EWM) in a counter-flow wet cooling tower. The research addresses gaps in existing literature, which often evaluates single packing types under idealized conditions, leading to suboptimal selections in industrial applications and increased energy and water consumption. NNU features irregular film paths promoting adaptive flow and turbulence for enhanced heat and mass transfer; DSW incorporates dual S-waves to optimize surface area, improve water distribution, and minimize pressure drop; while EWM provides intermediate turbulence via its expandable mesh structure for flexible airflow. Experiments were conducted using the SOLTEQ HE152 bench-top cooling tower at inlet water temperatures of 35°C, 43°C, and 50°C, with water flow rates varied from 25 to 200 kg/h under constant airflow. Key performance indicators, including tower characteristic (KaV/L or NTU), cooling efficiency, and energy consumption, were evaluated against liquid-to-gas (L/G) ratios. Results demonstrate that NNU achieves the highest average tower characteristic values (0.4036 at 35°C, 0.4873 at 43°C, and 0.5322 at 50°C) due to its adaptive flow paths. DSW exhibits superior cooling efficiency at lower temperatures (average 74.00% at 35°C) and the lowest energy consumption across all regimes (322.13 W at 35°C, 663.85 W at 43°C, and 774.74 W at 50°C), attributed to optimized surface area and reduced pressure drop. EWM performs well at intermediate temperatures but shows greater variability. Efficiency decreases while energy consumption increases with rising L/G ratios and temperatures. This research provides empirical guidelines for packing selection to optimize thermal performance, reduce operational costs, and align with Sustainable Development Goals (SDGs) related to energy efficiency (SDG 7) and water conservation (SDG 6).